Ketaatan Iman Perempuan Janda Berdasarkan: ( 2 Raja-Raja 4:1-7 ) - Trinitas Nuryani Dakhi; Novita Cyntia Situmorang (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2024)
In every situation and condition, faith is an attitude of heart and faithful obedience to God's Word. This article explores the dimensions of believers' faith when facing life's challenges and struggles, both internal and external. The focus is on how they can face it calmly, relying on God, so that they ultimately rise from these challenges and struggles, achieving victory with Him. Through serious strengthening of faith, every believer will be able to live each day without fear, worry and anxiety, facing all life's challenges with confidence and courage. This writing method uses a deductive method.